Constitutional Constraints on Public Debt in the Ecological Transition Era - Michele Lemme (The European Journal of Comparative Economics)
This article focuses on financing the necessary public expenditures to address the challenge of climate change faced by human societies, specifically examining the choice of public debt. Considering the already significant levels of public debt worldwide, this decision becomes particularly complex. Therefore, the article explores the instruments of public debt in the context of climate change, raising questions about the consequences of unwise public borrowing and wasteful public expenditure, and how to protect future generations from bearing the primary burden of public loans. The article further undertakes a scholarly examination of what constitutional law can contribute to the ongoing debate.